Three-dimensional visualisation and analysis of post-operative changes in the size and shape of the dental arch and palate - Trefný, P; Tauferová, E; Bálková, S (Acta chirurgiae plasticae, 2005)
In craniofacial surgery and orthodontics, three-dimensional computer models of the dental arch and palate have recently entered usage in diagnosis assessment, treatment planning, case presentations and evaluation of treatment progress and outcome. In this contribution, we show how effective visualisation and evaluation of changes in the size and shape of the dental arch and palate in a given patient can be performed using superimposition of two or more 3D computer models that record the condition before and after treatment. We also present a method of three-dimensional measurement of the dental arch and palate suitable for evaluation of treatment results within retrospective and prospective studies in larger samples of subjects.
Keywords: Imaging, Three-Dimensional; Postoperative Period; tělesné váhy a míry; zobrazování trojrozměrné; Body Weights and Measures; Models, Dental; stomatochirurgické výkony; Humans; Models, Anatomic; zubní modely; lidé; pooperační období; Oral Surgical Procedures; Palate; anatomické modely; patro; Dental Arch; zubní oblouk